The effect of individual exercise rehabilitation program on ischemic burden and cardiac function in patients with ischemic non-obstructive coronary heart disease: a randomized parallel controlled clinical trial - Wen, Yuan; Zhang, Yuanyuan; Lv, Qingquan; Lan, Weiqun; Shu, Yi; Qi, Qiuhuan; Hu, Hongping; Saleh, Othman Zakaria (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCoronary heart disease (CHD) is a pervasive chronic condition that poses a significant threat to global health and mortality worldwide. Given the severity of this disease, it is imperative to consider pivotal factors such as age, concurrent diseases, and physical frailty of patients diagnosed with ischemic non-obstructive CHD prior to initiating cardiopulmonary rehabilitation. Consequently, the objective of this study is to investigate the impact of an individualized exercise rehabilitation program, on the ischemic burden in patients suffering from ischemic non-obstructive CHD.MethodsFrom February 2019 to July 2021, a cohort of one hundred patients diagnosed with ischemic non-obstructive CHD were recruited and randomly allocated into two groups. The control group underwent a standard rehabilitation program, while the intervention group participated in an individualized exercise rehabilitation program. This program was tailored to each patient, with a 50% power intensity exercise prescription derived from the results of the patient's Cardiopulmonary Exercise Testing (CPET) evaluation. The therapeutic effect, total myocardial ischemic burden (TIB), the effective rate of TIB reduction, pulmonary function indices, cardiac function, and the incidence of adverse events compared between the two groups.ResultsThe intervention group demonstrated a higher effective rate. TIB in the intervention group was significantly reduced at the 1,2, and 4-week marks post-intervention and exhibited a higher effective rate of total myocardial ischemia load reduction. Post-intervention, there were improvements in the Forced Vital Capacity (FVC), Forced Expiratory Volume in one second (FEV1), and the FEV1/FVC ratio, with the intervention group showing higher values for these parameters. Cardiac function was enhanced following the intervention, with the intervention group displaying higher Left Ventricular Ejection Fraction (LVEF) and Carbon Monoxide (CO) levels, and a lower Left Ventricular End-Diastolic Dimension (LVEDD) compared to the control group (P < 0.05).ConclusionAn individualized exercise rehabilitation regimen for patients diagnosed with ischemic non-obstructive CHD can effectively compensate for the lack of physical activity. This regimen has demonstrated its ability to enhance the clinical therapeutic effect, reduce the total load of myocardial ischemia, improve pulmonary function indices and cardiac function, and decrease the incidence of cardiovascular adverse events. Clinical Trial Registrationidentifier (TJ-IRB20210716).